The patient’s perspective on proton radiotherapy of skull base meningioma: a retrospective cross-sectional survey - Seidensaal, Katharina; Sailer, Jonas; Harrabi, Semi B.; Gehlen, Johannes von; Seidensaal, Irina; Weykamp, Fabian; Bernhardt, Denise; Debus, Jürgen; Herfarth, Klaus (Frontiers in oncology, 2022)
Background Radiotherapy plays an important role in the management of skull base meningioma. The aim of the study was to investigate patient reported outcomes. Methods A questionnaire of 20 items was sent to 192 patients with meningioma of the skull base who have been treated with proton therapy at a single institution. The survey included dichotomous, scaling and open questions about symptoms, social distancing, rehabilitation, work, reintegration, limitations in recreational activities as well as daily life activities and correlating diagnoses. Additionally, symptoms were reported retrospectively by the patients at different time points. In total 128 patients (77.6%) responded. The median age at the time of RT was 55 years (range: 28-91); the majority was female (79%). The median time between the treatment of meningioma and the survey was 38.5 months (range: 7-100). Results The most common initial symptoms were visual impairment (N=65, 42.2%), dizziness (N=38, 29.7%), double vision (N=32, 25%). The most limiting symptom in daily life at the time of survey was fatigue (N=31, 24.2%); a significant proportion of patients reported depression as associated diagnosis (31.3%). Only 53% of patients reported occupational activity before treatment, this number did not increase with time. Only N= 40 (31.3%) and N=35(27.3%) patients reported no limitations in daily household chores or recreational activities by the disease and treatment. The course of cognitive function after treatment showed a temporary deterioration with subsequent improvement. Except for the improvement in emotional functioning most domains showed a temporary deterioration during radiotherapy, still the values reached after six months differed weekly or moderately from the initial values. Conclusion: Besides of neurological deficits, patients with skull base meningioma experience a variety of unspecific symptoms, which can be most limiting in daily life. Even successful treatment does not necessary translate into alleviation of those symptoms. A greater focus on the characterization of those symptom complexes is necessary. Greater focus on functional structures as the hippocampus might improve the results. Due to the retrospective character this study is hypothesis generating.
Gesehen am 21.09.2022